Legal Consultation and Education Support: Societal Protection Through the Law in Digital Transactions - Junus, Nirwan; Nur Mohamad Kasim; Nuvazria Achir; Lisnawati W. Badu; Mutia Cherawaty Thalib; Karlin Z. Mamu; Akbar Hidayatullah Daud (Edumedia Solution, 2025)
The growth of digital transactions in the pedesaan community frequently leads to various legal issues as a result of the lack of understanding regarding health and obligations for individuals. This service activity aims to provide concrete actions through counseling, education, and legal training to the people of Padengo Village, Dengilo District, Pohuwato Regency. The execution of the activity involves a variety of stakeholders, including the government, the military, TNI, and the general public as the main subject. Through this activity, the general public has a better understanding of the legal protections in digital transactions, whether they are being used as buyers or sellers. In addition, the training aims to make paralegals in the area strategic in enhancing the community's legal knowledge so they can be proactive in resolving the first issues in the community. This study emphasizes the importance of stakeholder collaboration in creating a safe and effective digital transaction system for the local population.